2016
DOI: 10.1248/bpb.b16-00134
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dimethyl Fumarate on an Oxidative Stress Model Induced by Sodium Nitroprusside in Mice

Abstract: Recent reports have shown that dimethyl fumarate (DMF) prevents brain damage induced by intracerebral hemorrhage and this beneficial effect is mediated by the nuclear erythroid 2 p45-related factor-2-antioxidant response element (Nrf2-ARE) pathway. However, the downstream mechanism underlying the activation of the Nrf2-ARE pathway is unclear. Here, we investigated the protective effect of DMF using an in vivo model of oxidative stress induced by sodium nitroprusside (SNP) and rat primary striatal cultures. Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…It may be responsible for neuroprotection [53]. Another effect of DMF may be associated with the activation of heme oxygenase-1 [146]. The use of a signaling pathway of the Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-related factor 2-antioxidant-responsive element (Keap1-Nrf2-ARE) in vivo and in vitro leads to the downregulation of OS and inflammation, activated by DMF which may protect the nervous tissue against subarachnoid hemorrhage induced brain injury in rats [147].…”
Section: The Relationship Between Immunomodulatory Therapy Os Anmentioning
confidence: 99%
“…It may be responsible for neuroprotection [53]. Another effect of DMF may be associated with the activation of heme oxygenase-1 [146]. The use of a signaling pathway of the Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-related factor 2-antioxidant-responsive element (Keap1-Nrf2-ARE) in vivo and in vitro leads to the downregulation of OS and inflammation, activated by DMF which may protect the nervous tissue against subarachnoid hemorrhage induced brain injury in rats [147].…”
Section: The Relationship Between Immunomodulatory Therapy Os Anmentioning
confidence: 99%
“…As a first-line treatment for multiple sclerosis, DMF can inhibit lipid peroxidation, and regulate free radical metabolism [28]. The findings from the present study showed that in STZ-induced hyperglycemic mice with experimental aortic atherosclerosis, DMF increased the expression of Nrf2, reduced aortic oxidation, and improved thoracic aortic endothelial function.…”
Section: Discussionmentioning
confidence: 53%
“…Previous mechanistic studies suggested that the therapeutic mechanism of DMF is mainly involved in Nrf-2-dependent regulation of oxidative stress [ 19 , 20 ]. A series of evidence have shown that Nrf-2 is beneficial for autoimmune disorders and inflammatory diseases, such as multiple sclerosis and neurodegenerative diseases [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous mechanistic studies suggested that the therapeutic mechanism of DMF is mainly involved in Nrf-2-dependent regulation of oxidative stress [19,20]. injected the mice at a dosage of 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%